Sulfonamide and tetracycline resistance genes in total- and culturable-bacterial assemblages in South African aquatic environments - Suzuki, Satoru; Ogo, Mitsuko; Koike, Tatsuya; Takada, Hideshige; Newman, Brent (Frontiers in Microbiology, 2015)
Antibiotic resistant bacteria (ARB) are ubiquitous in the natural environment. The introduction of effluent derived antibiotic resistance genes (ARGs) into aquatic environments is of concern in the spreading of genetic risk. This study showed the prevalence of sulfonamide and tetracycline resistance genes, sul1, sul2, sul3 and tet(M), in the total bacterial assemblage and colony forming bacterial assemblage in river and estuarine water and sewage treatment plants (STP) in South Africa. There was no correlation between antibiotic concentrations and ARGs, suggesting the targeted ARGs are spread in a wide area without connection to selection pressure. Among sul genes, sul1 and sul2 were major genes in the total (over 10-2 copies/16S) and colony forming bacteria assemblages (approx 10-1 copies/16S). In urban waters, the sul3 gene was mostly not detectable in total and culturable assemblages, suggesting sul3 is not abundant. tet(M) was found in natural assemblages with 10-3 copies/16S level in STP, but was not detected in colony forming bacteria, suggesting the non-culturable (yet-to-be cultured) bacterial community in urban surface waters and STP effluent possess the tet(M) gene. Sulfamethoxazole resistant (SMXr) and oxytetracycline resistant (OTCr) bacterial communities in urban waters possessed not only sul1 and sul2 but also sul3 and tet(M) genes. These genes are widely distributed in SMXr and OTCr bacteria. In conclusion, urban river and estuarine water and STP effluent in the Durban area were highly contaminated with ARGs, and the yet-to-be cultured bacterial community may act as a non-visible ARG reservoir in certain situations.